Forecasting by analogy on waste-to-energy technologies for future technology transfer in the Philippines some strategic dimensions - Hernandez, Diana Marie T. (University of the Philippines Diliman, Technology Management Center, 2010)
The purpose of this study is to determine the key factors, which contribute to the success or failure of the technology transfer experience of waste-to-energy projects in the Philippines and how can these factors influence future and similar initiatives. It focuses on the case of Quezon City Controlled Disposal Facility Biogas Emission Reduction Project and of Montalban Landfill Methane Recovery and Power Generation Project, the pioneering international technology transfer projects in the country on waste-to-energy technology. A forecasting by analogy was adopted as the methodology to analyze the case of the Philippines vis-a-vis a specific waste-to-energy project in China, which also involved transfer of technology. The case in China was chosen as the "model" project by which the case of the Philippines was compared because of the similarity in the situation of the two such that both are developing countries at the time of the initiation of the project that they required technology transfer from international sources to acquire the necessary technology. The case in China also specifically highlighted the factors, which contribute to its partial success. Climate change is considered as one of the serious challenges that are being faced worldwide. Both natural processes and human activities, which contribute in the increase in greenhouse gases that leads to stronger greenhouse effect, can cause climate change. It has an impact not only environmentally but also socially, financially and economically. Since 1980, there have been various efforts, which were initiated to help address the issue of climate change. A recent initiative by most governments of the world is to adhere to an international agreement, the United Nations Framework Convention on Climate Change (UNFCC), which aims to stabilize greenhouse gas concentrations in the atmosphere at a level that would prevent dangerous, man-made interference with the climate system. An economic mechanism, the Clean Development Mechanism (CDM), which encouraged the cooperation between developed and developing countries to facilitate the achievement of targets set by the earlier agreement, has also been introduced. One of the popular strategies used recently to address climate change is the application of renewable energy as it is a low-carbon technology. The use of municipal solid waste as a renewable source to produce energy is an example of the application of renewable energy. This process helps reduce greenhouse gas emission and therefore contributes to addressing climate change. Since the technology required to derive renewable energy is relatively new, developing countries often opt to transfer the technology from international sources to acquire and use it in their countries. Philippines, a developing country in Southeast Asia, also has its share of significant initiatives to help address climate change. It has institutionalized several programs and projects to support the fight against the adverse effect of climate change. Earlier, the country in particular suffers from poor solid waste management due to rapidly growing population and lack of adequate disposal sites. To address such, the country has adopted laws to ensure that the local governments will be responsible in handling their municipal waste.